Maize 16-kD γ-zein forms very unusual disulfide-bonded polymers in the endoplasmic reticulum: implications for prolamin evolution. (2nd August 2018) - Mainieri, Davide; Marrano, Claudia A; Prinsi, Bhakti; Maffi, Dario; Tschofen, Marc; Espen, Luca; Stöger, Eva; Faoro, Franco; Pedrazzini, Emanuela; Vitale, Alessandro
Abstract : A prolamin paralog generated upon maize whole-genome duplication has changed its polymerization and solubility properties, allowing a new function in the assembly of maize protein bodies. Abstract: In the lumen of the endoplasmic reticulum (ER), prolamin storage proteins of cereal seeds form very large, ordered heteropolymers termed protein bodies (PBs), which are insoluble unless treated with alcohol or reducing agents. In maize PBs, 16-kD γ-zein locates at the interface between a core of alcohol-soluble α-zeins and the outermost layer mainly composed of the reduced-soluble 27-kD γ-zein. 16-kD γ-zein originates from 27-kD γ-zein upon whole-genome duplication and is mainly characterized by deletions in the N-terminal domain that eliminate most Pro-rich repeats and part of the Cys residues involved in inter-chain bonds. 27-kD γ-zein also forms insoluble PBs when expressed in transgenic vegetative tissues. We show that in Arabidopsis leaves, 16-kD γ-zein assembles into disulfide-linked polymers that fail to efficiently become insoluble. Instead of forming PBs, these polymers accumulate as very unusual threads that markedly enlarge the ER lumen, resembling amyloid-like fibers. Domain-swapping between the two γ-zeins indicates that the N-terminal region of 16-kD γ-zein has a dominant effect in preventing full insolubilization. Therefore, a newly evolved prolamin has lost the ability to form homotypic PBs, and has acquired a new function in the assembly of natural, heteropolymeric PBs.